HYPERHOMOCYSTEINEMIA, A BIOCHEMICAL TOOL FOR ISCHEMIC VEIN OCCLUSION DURING ACUTE PHASE - Bassam Mubarik; Muhammad Adrees; Iftikhar Ahmad (Journal of University Medical & Dental College, 2018)
ABSTRACT: The purpose of study was to diﬀerentiate ischemic central retinal vein occlusion from non ischemic central retinal vein occlusion using homocysteine level as a biochemical marker during early stage of the disease. METHOD: Fasting plasma homocysteine level was measured in 50 patients with unilateral ischemic central retinal vein occlusion and compared with a total of 50 age matched patients with non ischemic central retinal vein occlusion patients and 50 age matched healthy control subjects. RESULTS: Homocysteine level was found signiﬁcantly increased in ischemic vein occlusion(27.1mmol/l)as compared to non ischemic vein occlusion (14.6 mmol/l) and control (12.8mmol/l) subject.(P< .05)